2020
DOI: 10.1590/1981-6723.25419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined hydrolyzed collagen and maltodextrin as carrier agents in spray drying of cocona pulp

Abstract: This work aimed to evaluate the effect of carrier agents containing maltodextrin and protein, represented by hydrolyzed collagen on the spray drying process of cocona (Solanum sessiliflorum Dunal), and on the properties of the resulting powders. We used pre-established proportions between the solids of cocona pulp and the carrier agents (P:CA), and among carrier agents themselves, maltodextrin and hydrolyzed collagen, (MD:HC). The process was carried out in a spray dryer at an inlet air temperature of 120 ºC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The other main peaks were obtained at 3575–2993, 2916, 2850, and 1736 cm −1 . The strong peaks at the 1500–500 cm −1 fingerprint region were mainly attributed to the carbohydrates (Cerit et al., 2023 ; Collazos‐Escobar et al., 2020 ; Vargas‐Muñoz & Kurozawa, 2020 ). The wide O‐H stretching vibration peaks were detected between 3575 and 2993 cm −1 corresponding to phenols and sugars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other main peaks were obtained at 3575–2993, 2916, 2850, and 1736 cm −1 . The strong peaks at the 1500–500 cm −1 fingerprint region were mainly attributed to the carbohydrates (Cerit et al., 2023 ; Collazos‐Escobar et al., 2020 ; Vargas‐Muñoz & Kurozawa, 2020 ). The wide O‐H stretching vibration peaks were detected between 3575 and 2993 cm −1 corresponding to phenols and sugars.…”
Section: Resultsmentioning
confidence: 99%
“…The other main peaks were obtained at 3575-2993, 2916, 2850, and 1736 cm −1 . The strong peaks at the 1500-500 cm −1 fingerprint region were mainly attributed to the carbohydrates (Cerit et al, 2023;Collazos-Escobar et al, 2020;Vargas-Muñoz & Kurozawa, 2020).…”
Section: Chocolate Propertiesmentioning
confidence: 99%
“…Padzil et al ( 28 ) also observed that the L * value of the treated purple sweet potato extract increased with the incorporation of MD as the MD initially has a white color ( L * = 98.18 ± 0.15), whereas the redness (+ a * ) of the treated purple sweet potato extract was significantly decreased as the concentration of MD increased. The increase in lightness and a reduction in chroma (color saturation) could be attributed to the dilution effect ( 55 ). The same trend was obtained for powdered pink guava with MD ( 56 ) and tamarind pulp with MD–SPI ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the characteristic bands at 1639 cm −1 and 1358 cm −1 can be attributed to the angular straining of OH bonds (referring to absorbed water) and angular straining of C-H bonds, respectively. Bands at 1147 cm −1 , 1076 cm −1 and 927 cm −1 were observed in the characteristic carbohydrate absorption region, referring to C-O-C and C-O deformations [ 54 , 55 ]. The microparticle spectra of beetroot soup microencapsulated in maltodextrin, regardless of the polysaccharide ratio used for microencapsulation, can be attributed predominantly to maltodextrin.…”
Section: Discussionmentioning
confidence: 99%